SAPS 3, APACHE IV or GRACE: which score to choose for acute coronary syndrome patients in intensive care units? - Antonio Paulo Nassar Junior; Amilcar Oshiro Mocelin; Fabio Moreira Andrade; Leonardo Brauer; Fabio Poianas Giannini; Andre Luiz Baptiston Nunes; Carlos Augusto Dias (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE Acute coronary syndromes (ACS) are a common cause of intensive care unit (ICU) admission. Specific prognostic scores have been developed and validated for ACS patients and, among them, GRACE (Global Registry of Acute Coronary Events) has had the best performance. However, intensive care clinicians generally use prognostic scores developed from heterogeneous populations of critically ill patients, such as APACHE IV (Acute Physiologic and Chronic Health Evaluation IV) and SAPS 3 (Simplified Acute Physiology Score 3). The aim of this study was to evaluate and compare the performance of these three scores in a non-selected population of ACS cases. DESIGN AND SETTING Retrospective observational study to evaluate three prognostic scores in a population of ACS patients admitted to three general ICUs in private hospitals in São Paulo. METHODS All patients with ACS admitted from July 2008 to December 2009 were considered for inclusion in the study. Score calibration and discrimination were evaluated in relation to predicting hospital mortality. RESULTS A total of 1065 patients were included. The calibration was appropriate for APACHE IV and GRACE but not for SAPS 3. The discrimination was very good for all scores (area under curve of 0.862 for GRACE, 0.860 for APACHE IV and 0.804 for SAPS 3). CONCLUSIONS In this population of ACS patients admitted to ICUs, GRACE and APACHE IV were adequately calibrated, but SAPS 3 was not. All three scores had very good discrimination. GRACE and APACHE IV may be used for predicting mortality risk among ACS patients.